Potential Dysfunctions and Pathologies of Human Resource Management in Hierarchical Structures for Example, the Police - Jóźwiak, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper will discuss the potential dysfunction and pathology of human resource management in hierarchical organizations for example the Police. First, a short description will be presented to the police as an institution of the conditioned by the specific nature of social importance assigned to it by the legislature tasks and hierarchical structure based on the military. The next step will be to present the most important findings of this article definitional and regulations. Will also be presented to the most common categories of personnel management irregularities. The next section will discuss the issue of people management dysfunction in the Police including the specific nature of this formation. The aim is to answer the question about the legitimacy and effectiveness of the current legal requirements and the forms and methods of human resource management in the field of prevention and combating dysfunction occurring in the structure of the Police. The whole was completed applications.